Identifikasi Bakteri Gram Negatif Penghasil Extended Spectrum Beta-Lactamase (ESBL) Pada Urin Pengguna Kateter di Ruang Rawat Inap Kelas III RSUD Dr. H Abdul Moeloek Bandar Lampung - Revina Rifda Amelia; Reyhan Anjani Putri; Tri Umiana Soleha (CV. Jasa Sukses Abadi, 2023)
Urinary catheterization is an action to insert a catheter into the patient's bladder through the urethra used in the hospital. The use of urinary catheters increases the risk of urinary tract infections (UTI) by about 5% every day. The incidence of nosocomial infection is 3 times higher in class III inpatients. According to research bacteria found as a cause of urinary tract infections due to urine catheters have a high enough potential to become a bacterium inhibiting Extended Spectrum Beta-Lactamase (ESBL). ESBL is a mutated β-lactamase enzyme, causing an increase in the enzymatic activity of β-lactamase, so that this enzyme can hydrolyze third generation sefalosporins and aztreonam. To find out the existence of ESBL-producing gram-negative bacteria in the catheter user urine in class III inpatients Dr. H. Abdul Moloek. This study used a categorical descriptive method with a cross sectional approach. The sample in this study were 22 patients who used catheters in class III inpatient rooms. Then the samples were tested for culture, biochemical tests and Double Disc Synergy Test. The results of a study of 22 patients undergoing a culture test found 4 patients with ESBL-producing gram-negative bacteria, 3 Escherichia coli bacteria (75%) and 1 Pseudomonas aeruginosa bacterium (25%) %), from these results the most bacteria producing ESBL is Escherichia coli. The conclusion is the highest amount of ESBL-producing bacteria was Escherichia coli (75%).